KADAR ZAT GIZI BERAS DAN NASI LIMA VARITAS PADI UNGGUL - Dewi Sabita Slamet; Muhammad Enoch; J. Krisdinamurtirin; Mien K. Mamud; Ignatius Tarwotjo (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1971)
Kadar zat gizi beras dan nasi lima varitas padi unggul (The  nutrient  contents  of  raw and cooked rice of five high-yielding varieties). The nutrient contents of five high-yielding rice varieties namely PB S (IRRI 5), PB 8 (IRRI 8), C4-63, Dcwi Ratih and Shinta, did not differ significantly, except the protein content of C4-63 which was 9%, the highest. Processing of rice by milling, pounding, and pounding followed by parboiling had little influence on the nutrient content. Cooking of rice did not cause substantial reduction of nutrient content, except vitamin Bl.